REVIEW ARTIKEL: PENINGKATAN KELARUTAN SENYAWA OBAT ANTIMALARIA MENGGUNAKAN METODE MODIFIKASI KO-KRISTAL - Hasna; Hermanto, Faizal (Jurnal Buana Farma, 2024)
Malaria is an infectious disease caused by the Plasmodium parasite that infects humans through the bite of female Anopheles mosquitoes. Most antimalarial drugs have limitations in terms of solubility. Drug solubility is a very important parameter that determines the effectiveness of the drug, with good drug solubility, the drug can achieve optimal bioavailability and pharmacological effects, based on this, efforts are needed to overcome these problems in order to provide effective and efficient therapy to patients using existing antimalarial drugs that have been modified in their physicochemical properties so that their solubility increases. The purpose of this study was to review various studies that used the co-crystal modification method to increase the solubility of antimalarial drug compounds. This study was designed using the Narrative Review method, article searches were carried out using two databases, namely Google Scholar and PubMed, with the keywords "Co-crystal" OR "Antimalaria". In this study, 7 articles were found that met the inclusion and exclusion criteria. The selected articles are articles that discuss antimalarial drugs (artesunate, artemisinin, pyrimethamine) developed by the co-crystal method which experienced a multi-fold increase in solubility compared to its pure preparation. The co-crystal method can be a solubility enhancing solution for antimalarial drugs that have low solubility in water, increasing the solubility of antimalarial drugs causes the bioavailability of the drug to increase, so that the drug can provide good therapeutic effects.